The Influence of Service Quality and Product Quality on Consumer Purchasing Decisions at HokBen Mall Bassura - Siti Junaedah; Dhuha Safria; Mentari Pratami (Takaza Innovatix Labs Ltd., 2026)
Competition in the fast food restaurant industry encourages companies to improve service quality and product quality to maintain consumer purchasing decisions. This study aims to analyze the influence of service quality and product quality on consumer purchasing decisions at HokBen Mall Bassura, both partially and simultaneously. The study uses a quantitative approach with a descriptive method. The study population is all consumers of HokBen Mall Bassura, while the sample is 110 respondents selected using accidental sampling techniques. Data were collected through Likert-scale questionnaires, observation, and documentation. Data analysis was carried out using SPSS through validity tests, reliability tests, classical assumptions, multiple linear regression, t-tests, F-tests, and coefficients of determination. The results show that service quality has a positive and significant effect on purchasing decisions with a t-value of 4.867 and a significance of 0.000, while product quality has a positive and significant effect with a t-value of 7.937 and a significance of 0.000. Simultaneously, both variables have a significant effect on purchasing decisions with an F-value of 34.709 and are able to explain 38.2% of the variation in purchasing decisions. This study concludes that consistently improving service quality and product quality can improve consumer purchasing decisions, with product quality having a more dominant influence than service quality